Midterm prognosis following total correction of tetralogy of fallot in adult patients - Khajali, Zahra; Mohammadi, Nasibeh; Toloueitabar, Yaser; Maleki, Majid; Saedi, Sedigheh; nourouzi, Zeinab; Mazloum-Zadeh, Saeideh; Chenaghloo, Maryam; Jalali, Amirhossein; Tatari, Hassan; Aliramezany, Maryam (Frontiers in Cardiovascular Medicine, 2023)
Background Tetralogy of Fallot is a common congenital heart disease characterized by cyanosis. The primary treatment approach involves corrective surgery typically performed within the first year of life to achieve complete resolution. However, certain patients may undergo surgery at an older age. This study seeks to assess the efficacy of surgery by examining the midterm outcomes of total correction of Tetralogy of Fallot when performed in older individuals. Methods This interventional-longitudinal study focused on patients who underwent complete surgery to correct tetralogy of Fallot at an advanced age of over 15 years. All of the participants were referred to the Shahid Rajaei Heart and Vascular Center, which is a referral center for congenital heart diseases in Iran, between 2010 and 2020. The surgical procedures for these patients involved primary total correction of tetralogy of Fallot or surgery following by shunt implantation. Prior to the surgery, the necessary information was gathered from the patients' medical records. The patients were then monitored over a 5-year period, during which they received regular check-ups from cardiologist with fellowship in adult congenital heart disease. Results A total of 94 participants were enrolled in the study, with an average age of 26.7 ± 9.6 years. Notably, the majority of the participants were male. The study reported a late mortality rate of 3.2%. Furthermore, 17 patients, constituting 18% of the cohort, underwent a secondary surgical procedure. This secondary surgery encompassed 14 cases of Pulmonary Valve Replacement (14.8%) and 3 cases of Ventricular Septal Defect repair (3.1%). Conclusion While the optimal age for total correction of Tetralogy of Fallot is conventionally considered to be within the first year of life, this study demonstrated that surgical intervention performed at a later stage of life can yield favorable midterm prognoses. It is imperative to emphasize that individuals unable to undergo surgery at the ideal age due to a multitude of factors should not be deprived of the potential benefits associated with surgical intervention.